A GENEALOGY OF BLACK ORGANIZING IN BRAZIL - Reiter, Bernd (REVISTA NERA, 2012)
This article argues that the vast literature on “new social movements” misrepresents the historicity of identity-based organization in Latin America. Such organizing is indeed much older than the literature suggests. To prove this argument, I provide a genealogy of black, identitybased organizing in Brazil. This genealogy makes clear that black organizing started when Africans first arrived in Brazil. To explain the ebbs and flows of this organizing, the theoretical frameworks of Sidney Tarrow and Susan Epstein, who focus on political opportunities and changing repertoires, respectively, prove to be more useful.